2009
DOI: 10.1089/ten.tea.2008.0295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber Diameter and Alignment of Electrospun Polyurethane Meshes on Mesenchymal Progenitor Cells

Abstract: Effective strategies to guide cell alignment and the deposition of an oriented extracellular matrix are critical for the development of anisotropic engineered tissues suitable for the repair of ligament defects. Electrospinning is a promising means to create meshes that can align adherent cells, but the effect of fiber mesh architecture on differentiation has not been examined closely. Therefore, the goal of this study was to determine the effect of fiber diameter and the degree of fiber alignment on mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
188
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(199 citation statements)
references
References 52 publications
11
188
0
Order By: Relevance
“…Advanced manufacturing techniques can be used to control the spatial sub-micrometric internal architecture in engineered tissues, manipulating the scaffold topography on the length scale of the stem cell niche and smaller. It has been demonstrated that nanofibrous polymeric scaffolds offer to the cells biomimetic configurations that resembles ECM collagen fibers in their ability to support the differentiation of progenitor/stem cells along adipogenic, chondrogenic, and osteogenic lineages (Yang, Murugan et al 2005;Badami, Kreke et al 2006;Bashur, Shaffer et al 2009;Wise, Yarin et al 2009). Nanotechnology, or the use of nanomaterials, may help to realize materials mimicking surface properties (including topography, energy, etc) of natural tissues.…”
Section: Design Of the Architectural Structurementioning
confidence: 99%
“…Advanced manufacturing techniques can be used to control the spatial sub-micrometric internal architecture in engineered tissues, manipulating the scaffold topography on the length scale of the stem cell niche and smaller. It has been demonstrated that nanofibrous polymeric scaffolds offer to the cells biomimetic configurations that resembles ECM collagen fibers in their ability to support the differentiation of progenitor/stem cells along adipogenic, chondrogenic, and osteogenic lineages (Yang, Murugan et al 2005;Badami, Kreke et al 2006;Bashur, Shaffer et al 2009;Wise, Yarin et al 2009). Nanotechnology, or the use of nanomaterials, may help to realize materials mimicking surface properties (including topography, energy, etc) of natural tissues.…”
Section: Design Of the Architectural Structurementioning
confidence: 99%
“…Advanced manufacturing techniques can be used to control the spatial sub-micrometric internal architecture in engineered tissues, manipulating the scaffold topography on the length scale of the stem cell niche and smaller. It has been demonstrated that nanofibrous polymeric scaffolds offer to the cells biomimetic configurations that resembles ECM collagen fibers in their ability to support the differentiation of progenitor/stem cells along adipogenic, chondrogenic, and osteogenic lineages (Yang, Murugan et al 2005;Badami, Kreke et al 2006;Erisken, Kalyon et al 2008;Bashur, Shaffer et al 2009;Wise, Yarin et al 2009). Nanotechnology, or the use of nanomaterials, may help to realize materials mimicking surface properties (including topography, energy, etc) of natural tissues.…”
Section: Design Of the Architectural Structurementioning
confidence: 99%
“…However, these materials-typically prepared by melt-or wetspinning-consist of 25-200 lm diameter fibers that are larger than mammalian cells and do not necessarily present a topography to guide cell alignment. In contrast, fibers produced by electrospinning have diameters of 0.1-5 lm [8], can guide cell alignment [9][10][11], and modulate development of organized extracellular matrix (ECM) [12][13][14]. For example, Chaurey et al showed that as the diameters of aligned fibers were increased from 0.1 to 0.8 lm, the cell alignment also increased [15].…”
Section: Introductionmentioning
confidence: 99%